The law of God, the law of the State and the law of Crime: an anthropological account of the consolidation of multiple normative regimes in Brazilian urban margins - Maldonado, Janaina (2024)
In Brazil’s poor urban areas, the state is not the sole producer of ‘law and order’ or monopoliser of the legitimate use of force. A multiplicity of authorities coexist and interact, and much of the dynamics of violence and urban order emerge from this tense interplay. Based on ethnographic fieldwork in Brazilian urban peripheries, this article proposes a theoretical reflection on normative multiplicities and their relations to the dynamics of violence in contexts of sharp conflict. Two main arguments are presented: 1 - that the processes of Brazil’s recent history have culminated in a specific social configuration of normative pluralism in the country’s urban peripheries, where the state, religion and crime act as coexisting authorities; and 2 - that this plurality is sustained by a triple paradigm: respectability, material bases and the capacity and will to use violence. Theoretically, therefore, we have sought to develop the concept of ‘normative regimes’ and the triple paradigm that underpins their formation. In doing so, we hope to contribute to the social science debate on plural governance.